TAFSIR OF THE QUR'AN AND THE ROLE OF ULAMA IN PROMOTING THE CONTENT OF THE QUR'AN BASED ON ISLAMIC EDUCATION - Ahmad Zuhri (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Understanding the interpretation of the Qur'an as the basis for the life of Muslims is very important. This refers to the rules and regulations that apply the Islamic religion to all aspects of Muslim life. Several steps that can be implemented in understanding the content and interpretation of the Qur’an are using an independent method by reading various literature recommended or written by commentators, or even following studies on the interpretation of the Qur’an, both formal and non-formal, that have been carried out in various forms, both in writing and orally. These efforts are not only about reaching certain targets among the common people; they must also be among the elite and community leaders, so that they will not only be recipients of knowledge about the Qur'an but also presenters and givers. This effort must be developed and increased again in the future in order to make the Qur'an a source of nur, huda, and dhikr for the people as a whole.